Design of a two-seater seaplane wing spar structure with composite materials - Bunyawanichakul, Phacharaporn; Suraratchai , Monchai; Krajangsawasdi, Narongkorn (Journal of Applied Research on Science and Technology (JARST), 2024)
A two-seater, mono-wing seaplane was initially developed for survey and rescue operations, with an empty weight of 470 kg and a maximum takeoff weight of 650 kg. Fiber-reinforced composite materials, consisting of fiber reinforcement and thermosetting polymer, were used in this airframe to reduce weight because the structural properties can be customized by adjusting the orientation of the fiber fabric layup and removing redundant material, which is impossible with metal. This paper presents a comprehensive overview of the design process for the aircraft's primary I-beam wing spar, employing composite material. Before conducting design calculations, it is critical to consider the variability of characteristics of composite materials caused by fabrication conditions such as temperature, humidity, and defects. As a result, it is imperative to conduct thorough testing of carbon fiber-reinforced composites following many different testing requirements. The coupon tests capture critical characteristics such as strength, stiffness, and Poisson's ratio across several orientations. The wing spar I-beam structure was subsequently developed with three primary considerations: stiffness (maximum deflection), strength, and stability (structural buckling). Following preliminary sizing of the I-beam wing spar, a simple initial layup was recommended, with primary loading in each component. The initial design was then subjected to a more detailed calculation using classical lamination theory, which took into account distributed load along the wing, spar taper, ply-drops along the span, and composite layup guidelines in order to reduce structural weight while ensuring the main spar's ability to withstand operational loads effectively. The calculating results show that the spar with an optimized composite design has a lighter weight than the original design by around 43%, while it can withstand the same loads with no analytical failure.